2016
DOI: 10.1007/s00354-016-0304-0
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal Altruism-based Cooperation in a Social Network Game

Abstract: Cooperative behaviors are common in humans and are fundamental to our society. Theoretical and experimental studies have modeled environments in which the behaviors of humans, or agents, have been restricted to analyze their social behavior. However, it is important that such studies are generalized to less restrictive environments to understand human society. Social network games (SNGs) provide a particularly powerful tool for the quantitative study of human behavior. In SNGs, numerous players can behave more… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…They are useful for constructing theoretical models of social phenomena. Studies (Arnaboldi et al, 2012;Song et al, 2012;Fujihara and Miwa, 2014;Hossmann et al, 2011;Arnaboldi et al, 2013b;Hu et al, 2012;Takano et al, 2016a;Saramaki et al, 2014;Dunbar, 2016;Takano et al, 2016b) previously cited in this paper have also analysed data from SNSs, mobile phones, social network games, and SMSs.…”
Section: Introductionmentioning
confidence: 99%
“…They are useful for constructing theoretical models of social phenomena. Studies (Arnaboldi et al, 2012;Song et al, 2012;Fujihara and Miwa, 2014;Hossmann et al, 2011;Arnaboldi et al, 2013b;Hu et al, 2012;Takano et al, 2016a;Saramaki et al, 2014;Dunbar, 2016;Takano et al, 2016b) previously cited in this paper have also analysed data from SNSs, mobile phones, social network games, and SMSs.…”
Section: Introductionmentioning
confidence: 99%
“…Channel co-ordination (Cui et al, 2007), revenue management (Tereyağoğlu et al, 2017), procedural fairness (Rabin, 1993), advantage and disadvantage fairness (Fehr and Schmidt, 1999) and fairness preference model (Bolton and Ockenfels, 2000; Cui and Wu, 2018) Forecast bias Different means of forecast bias (Goodwin et al, 2018), overconfidence (overplacement, overestimation and over-precision) (Gervais et al, 2003;Moore and Healy, 2008) Reciprocity and altruism Positive and negative reciprocity (Fehr and Gächter, 2000;Pereira et al, 2006;Gal and Pfeffer, 2007), corporate social responsibility (Luo and Zheng, 2013), supply chain co-operation (Simatupang and Sridharan, 2005;Liang and Wan, 2007), supply chain co-ordination (Lin and Hou, 2014;Du et al, 2014), optimal decision making (Xia et al, 2018;Shi et al, 2018;Liu, Yan, X., Wei, Xie and Wang, 2018), order allocation (Baltacioglu et al, 2007;Zhang, Li and Gou, 2017) and altruistic behaviour and subtypes (Takano et al, 2016)…”
Section: Fairness Concernmentioning
confidence: 99%
“…The game allows real players to cooperate and compete with others in situations where the player's benefit is represented by a quantitative value, such as a payoff in game theory. A previous study [29] demonstrated the existence of reciprocal relationships where cooperators had more advantages than non-cooperators in this SNG.…”
Section: Introductionmentioning
confidence: 61%